2003
DOI: 10.1152/ajpcell.00338.2002
|View full text |Cite
|
Sign up to set email alerts
|

VACM-1, a cul-5 gene, inhibits cellular growth by a mechanism that involves MAPK and p53 signaling pathways

Abstract: Vasopressin-activated Ca2+-mobilizing (VACM)-1 gene product is a 780-amino acid membrane protein that shares sequence homology with cullins, a family of genes involved in the regulation of cell cycle. However, when expressed in vitro, VACM-1 attenuates basal and vasopressin- and forskolin-induced cAMP production. Mutating the PKA-dependent phosphorylation site in the VACM-1 sequence (S730AVACM-1) prevents this inhibitory effect. To further examine the biological role of VACM-1, we studied the effect of VACM-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Heterologous CUL5 expression has been reported to exert an antiproliferative effect (32,33). Furthermore, a clinical study showed a significant decrease in CUL5 expression in breast tumors versus matched normal tissue (34).…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous CUL5 expression has been reported to exert an antiproliferative effect (32,33). Furthermore, a clinical study showed a significant decrease in CUL5 expression in breast tumors versus matched normal tissue (34).…”
Section: Discussionmentioning
confidence: 99%
“…The purified ASB2 complex was incubated with various combinations of Uba1, Ubc5a, GST-Ubiquitin (GST-Ub) in the absence or presence of ATP to assess its ability to stimulate ubiquitination by Ubc5 by Western blot using anti-GST antibodies. more, expression of Cul5 protein inhibits cell growth and retards cytokinesis by a mechanism that involves p53 (43). Although the mechanism by which Cul5 functions in these processes remains unclear, Cul5-containing ECS ubiquitin ligases have been shown to regulate the turnover of molecules involved in cell-cycle control.…”
Section: Discussionmentioning
confidence: 99%
“…Three G-protein coupled receptors (V1a, V1b, and V2) mediate the biological influence of AVP [2,3]. Additionally, the vasopressin-activated calcium mobilizing (VACM) protein has been described as a putative AVP receptor, although very little is known about its role in cell function [4]. Generally, signaling through the V1 receptors can involve the activation of phospholipase A2, C, D, and protein kinase C, leading to an increase in intracellular free Ca 2+ , and the activation of the mitogen-activated protein kinase (MAPK) and focal adhesion kinase (FAK).…”
Section: Introductionmentioning
confidence: 99%